Insistence on sameness and broader autism phenotype in simplex families with autism spectrum disorder. Issue 9 (5th October 2018) - Esler, Amy N.; Stronach, Sheri T.; Jacob, Suma
Abstract : Insistence on sameness (IS) in individuals with autism spectrum disorder (ASD) and their families may have utility in identifying meaningful subgroups for studying the pathophysiological and genetic pathways affected in ASD. The primary objectives of the current study were to (1) characterize features of IS in parents of children with ASD and (2) examine their relationships with child IS symptoms. Participants were 2760 families who participated in the Simons Simplex Collection. Levels of parent IS were measured using the Broader Autism Phenotype Questionnaire (BAPQ). A factor analysis generated a BAPQ‐IS scale, consisting of a subset of 11 items from the original BAPQ‐Rigid scale. Correlations were run to examine the relationship between parent BAP and child IS variables. Correlations were found between parent IS and measures of child IS. Although relationships between parent and child IS features were statistically significant in this large sample, effect sizes were small. Results may be reflective of sample design that only included simplex families, where ASD severity may be predominantly driven by spontaneous mutations and less by common inherited risk from parents. In addition, child and parent measures used may have differentially captured features and severity of IS. Further research is needed on how IS can be accurately measured throughout development and across individuals with ASD and their unaffected family members to facilitate future studies on IS as a possible endophenotype for ASD. Autism Res 2018, 11: 1253–1263 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Previous research has suggested that insistence on sameness (IS) may be a heritable trait in autism spectrum disorder (ASD). The study examined whether children with high levels of IS had parents with IS tendencies. A small relationship was found between parent and child measures of IS. Future research is needed on measurement of insistence on sameness across individuals with and without ASD to further examine this relationship and improve understanding of the genetics of ASD.